Determining amino acid requirements in humans - Paoletti, Alyssa; Courtney-Martin, Glenda; Elango, Rajavel (Frontiers in Nutrition, 2024)
Amino acids form the building blocks of body protein. Dietary protein sources provide the amino acids needed, but protein sources vary widely in amio acid composition. To ensure humans can meet body demands for amino acids, amino acid intake recommendations are provided by the Dietary Reference Intakes (DRI) and by Food and Agriculture Organization/World Health Organization/United Nations University (FAO/WHO/UNU). Current amino acid intake recommendations, however, are based on data collected predominantly from young adult males. The development of the minimally invasive indicator amino acid oxidation(IAAO) method has permitted the evaluation of amino acid requirements in various vulnerable populations. The purpose of this review is to discuss recent amino acid requirement studies in school-age children, pregnant females and the elderly determined using the IAAO technique. These requirements will help to inform evidence-based recommendations that will help to guide dietary guidelines.